Global Fields, Institutional Emergence, and the Regulation of Transnational Corporations. (30th April 2020) - Lim, Alwyn
Abstract: World society theory has developed to become a major sociological perspective on globalization, focusing on the diffusion of global institutions and increasingly on the domestic impact of those institutions. Nevertheless, the emergence of global institutions has received less attention, raising questions about whether core elements of world society—institutional structures, actorhood, legitimacy—are sufficient to also explain how global institutions arise. This article proposes a "global fields" approach in which institutional emergence is conditional on the interaction between state and non-state actors around the exercise of international authority. Using archival United Nations (UN) data, I demonstrate this field approach through an historical review of global efforts in the UN to build a framework for the regulation of transnational corporations. In the 1970s, developing countries mobilized around a New International Economic Order, arguing that regulating foreign investment would contribute to economic justice. These efforts failed to establish a new globalization because state actors mobilized around national interests, state power, and centralized hierarchical regulation. Subsequently, in the 1990s, non-state actors were more successful in establishing the Global Compact, a global framework for corporate social responsibility, as they emphasized transcendent purposes, voluntarism, and collaboration. This case demonstrates the utility of a global fields approach to institutional emergence by highlighting the importance of how global fields structure interests, participation, strategies, and outcomes in global processes. The article concludes by discussing the theoretical implications of a global fields approach for the world society perspective and studies of the origins of global processes.